An Analysis of the Impact of Flash Floods on the Economic Welfare of the Community in Batang Toru From the Perspective of Maqasid Sharia - Rizalul Muslih Syawaluddin Hsb; Maryam Batubara; Muhammad Arif (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study analyzes the factors causing landslides and flash floods and their impact on the economic well-being of communities in Batang Toru District, South Tapanuli Regency, from the perspective of Maqasid Sharia. It was prompted by the flash flood disaster of 25 November 2025, which resulted in fatalities, infrastructure damage, loss of productive assets, and disruption of social-economic activities. This qualitative field research collected data through in-depth interviews, observation, and documentation involving the village head, the Regional Disaster Management Agency (BPBD), and affected residents, analyzed using the Miles, Huberman, and Saldaña interactive model. The findings show that the disaster was caused by the interaction of extreme rainfall, steep topography, the overflow of the Batang Toru River, land-use change, and river sedimentation. The disaster significantly affected economic well-being through damaged farmland, lost productive assets, halted economic activity, declining household income, heightened health risks, and disrupted children's education. From the Maqasid Sharia perspective, these impacts touch all five essential objectives of sharia: hifz al-din, hifz al-nafs, hifz al-'aql, hifz al-nasl, and hifz al-mal. Mitigation, emergency response, and rehabilitation efforts by the government, BPBD, and the community reflect the implementation of Maqasid Sharia values, although economic recovery still requires strengthening through environmental-conservation-based mitigation policy and post-disaster economic empowerment programs.